A Perspective Analysis of Students, Teachers and Physics Teachers Candidates about Asesmen Kompetensi Minimum (AKM) (Universitas Negeri Surabaya, 2022)
Asesmen Kompetensi Minimum (AKM) is one device used to measure students' ability. This study aims to tell students, teachers and physics teachers candidates about AKM. This study used a mixed method design at SMAN 17 Surabaya and Universitas Negeri Surabaya by giving questionnaires and interviews. The study was implemented from November 25 to December 7 2021, with 103 respondents. The quantitative data analysis technique used Kaiser-Meyer-Olkin (KMO) and Bartlett's test include Cronbach's Alpha Coefficient test, while the data qualitative used reduction, presentation and conclusion. Based on the results of the analysis of research data obtained on the Kaiser-Meyer-Olkin test (KMO) and Bartlett's of 0,691 and 0,584, while in Cronbach's Alpha Coefficient of 0,782 and 0,752. Thus this study is valid and reliable. The perspectives of students, teachers and physics teachers candidates agree with implementing the AKM as a substitute for the National Examination. Respondents stated that the AKM was more complex than the National Examination. However, the AKM cannot be used as a graduation requirement and a reference basis for formulating education in Indonesia because it is still being implemented. Need some preparation before implementation of AKM, such as guiding students. AKM can be integrated into physics learning. In this case, physical theory is associated with everyday life. Research that discusses the results of AKM implementation is a little bit. Based on the results of the research can be concluded that students, teachers and physics teachers candidates disagree with the AKM as the basis for reference and graduation requirements. Physics problems can be used as an AKM associated with the environment. Research related to the results of AKM implementation is not too much, so the research needs to follow up. Keywords: Asesmen Kompetensi Minimum, perspective, students teachers and physics teachers candidates